A wideband mmWave microstrip antenna based on zero‐mode and TM‐mode resonances. Issue 8 (3rd May 2022) - Luo, Yong; Gu, Yunlong; Zhang, Hao; Xu, Jiayou; Qian, Feng; Yang, Guangli; Cui, Hengrong
Abstract: Millimeter‐Wave (mmWave) antennas for 5G communication require wide bandwidth, directional radiation patterns, low‐profile design and multilayer compatibility for module‐level integration. In this paper, we introduce a method of loading shorting pins to a patch antenna to generate extra zero modes. By merging the 2nd zero‐mode, TM01 mode, 3rd zero‐mode, and TM20 mode in the frequency spectrum, a wide bandwidth varying from 23 to 34 GHz and a low‐profile as 0.762 mm can be obtained. Based on this wideband patch antenna, a 4 × 2 antenna array is obtained with the ±40° scanning performance. Theoretical analysis, full‐wave simulations, and experimental performances are presented, validating the effectiveness of this method to achieve a wideband performance in mmWave band. It can be applied to 5G communication systems in mmWave band.